Vadensea (Icacinaceae), a new genus to accommodate continental African species of Desmostachys - Jongkind, Carel C.h.; Lachenaud, Olivier (Phytotaxa, 2019)
The African genus Desmostachys s.l. is split in two, Desmostachys s.s. from Madagascar and the Comoros, with one species, and the new genus Vadensea from continental Africa, with four species. A synopsis of the latter genus is presented, with the necessary new combinations and the description of a new species, Vadensea testui. Desmostachys is characterised by asymmetrical and compressed pyrenes with a bumpy endocarp, petals glabrous inside and free, a linear stigma, a 5-lobulate disk, inflorescences with spirally arranged flowers and bracts present at most nodes, and a climbing habit. Vadensea has the pyrenes symmetrical, not compressed and with a reticulate endocarp, the petals hairy inside and often connate, a capitate stigma, a disk either cupular or absent, inflorescences with distichously arranged flowers and bracts absent or present at the lowest node only, and a usually arborescent or shrubby habit (occasionally climbing in one species).